2009
DOI: 10.1017/s0022377808007654
|View full text |Cite
|
Sign up to set email alerts
|

Large-amplitude electrostatic solitary structures in dusty plasmas with vortex-like variable charge dust distribution and non-isothermal trapped electrons

Abstract: The recent analysis of large-amplitude solitary potentials in a charge varying dusty plasma with trapped dust particles (Tribeche, M. 2005 Phys. Plasmas 12, 072304) is extended to include the electron trapping self-consistently. The nonisothermal trapped electron charging is investigated based on the orbit motion limited approach. It is found that the nonlinear localized potential structure enlarges when the electrons deviate from isothermality. The effect of this deviation is more significant under certain co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In response to the change in local electrostatic potential, as well as the plasma density, the charge of dust will be variable. 12) The presence of highly charged dust grains causes a series of impacts both in the sheath structure and the sheath formation. [13][14][15][16][17][18] For example, Ma and Yu 13) demonstrated that dust can narrow the sheath to a few Debye lengths, and that the varying charge of dust plays a vital role in the progress of sheath formation.…”
Section: Introductionmentioning
confidence: 99%
“…In response to the change in local electrostatic potential, as well as the plasma density, the charge of dust will be variable. 12) The presence of highly charged dust grains causes a series of impacts both in the sheath structure and the sheath formation. [13][14][15][16][17][18] For example, Ma and Yu 13) demonstrated that dust can narrow the sheath to a few Debye lengths, and that the varying charge of dust plays a vital role in the progress of sheath formation.…”
Section: Introductionmentioning
confidence: 99%